18F-FDG PET/CT imaging of relapsing polychondritis: A case report. Issue 33 (August 2016) - Zhou, Huijun; Su, Minggang; Li, Lin
Abstract: Background: Relapsing polychondritis (RP) is an uncommon autoimmune inflammatory disease that may affect cartilage throughout the body. Case report: We report on a case of fever of unknown origin in which 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) was performed to make a diagnosis of RP. Conclusion: Our case demonstrates that the use of 18F-FDG PET/CT is a useful diagnostic tool to accurately determine the extent of inflammation throughout the body which can be identified by an increased 18F-FDG uptake.